Preliminary study on diversity and abundance of Ichneumonids and Braconids (Insecta: Hymenoptera) at the Ayer Hitam Forest Reserve - Abu Bakar, Idris; Sajap, Ahmad Said; Hanida, Noor Farikha; A. B., Yaakob (Universiti Putra Malaysia Press, 2001)
A preliminary study on diversity and abundance of ichneumonids and braconids (Insecta: Hymenoptera) oj Ayer Hitam Forest Reserve (AHFR) oj Universiti Putra Malaysia was conducted Jrom 4 - 11 April 2000. Results showed that AHFR houses a variety of ichneumonid and braconid species. Generally, the ichneumonids were nearly twice as abundant and diverse than braconids. However, both insect groups were significantly more diverse in the middle than in the Forest fringes. Two more additions of ichneumonid subFamilies (Adelognathinae and Orthopelmatinae) for Malaysia were discovered from this Forest.